THE ROLE OF STUDENTS’ METACOGNITIVE AWARENESS IN MAKING DECISION CONCERNING ENVIRONMENTAL POLLUTION - Kusumastuti, Mimin Nurjhani; Yani, Mely; Rahman, Taufik (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
As human undoubtedly plays a role in today’s environmental problems, human inarguably must take control in overcoming them. Therefore, understanding how we can support the students in developing the ability to make environmentally friendly decisions is an essential part of an educational program. In this article, we evaluated the state and the role of metacognitive awareness as a factor that might affect junior high schools students in making a decision concerning environmental pollution, mainly the use of plastics in their everyday life.